THE ABORTION AS A PUBLIC HEALTH PROBLEM IN PERU - Távara, Luis (2015)
The word abortion brings a series of images and controversies. Before this term, much of the public tends to react in an emotional and often irrational. From the medical point of view, abortion is the termination of pregnancy before 22 weeks of gestation or before the child reaches 500 grams. It can be spontaneous or induced.